Effect of Climate Conditions and Plant Developmental Stage on the Stability of Antibodies Expressed in Transgenic Tobacco - Stevens, Lucas H. (American Society of Plant Physiologists, 2000)
Plants are regarded as a promising system for the production of heterologous proteins. However, little is known about the influence of plant physiology and plant development on the yield and quality of the heterologous proteins produced in plants. To investigate this, tobacco (Nicotiana tabacum cv Samsun NN) was transformed with a single construct that contained behind constitutive promotors the light- and heavy-chain genes of a mouse antibody. The in planta stability of the antibody was analyzed in transgenic plants that were grown under high and low irradiation at 15°C and 25°C. High-light conditions favored the production of biomass, of total soluble protein, and of antibody. The plants grown at 25°C developed faster and contained less antibody per amount of leaf tissue than the plants grown at 15°C. Both endogenous protein and antibody content showed a strong decline during leaf development. The heavy chains of the antibody underwent in planta degradation via relatively stable fragments. In vitro incubations of purified plantibody with leaf extracts of wild-type tobacco indicated the involvement of acidic proteases. It is interesting that the same antibody produced by mouse hybridoma cells exhibited higher stability in this in vitro assay. This may be explained by the assumption that the plant type of N-glycosylation contributes less to the stability of the antibody than the mouse-type of N-glycosylation. The results of this study indicate that proteolytic degradation during plant development can be an important factor affecting yield and homogeneity of heterologous protein produced by transgenic plants.